The Relationship Between the Use of Intrauterine Device and the Incidence of Ectopic Pregnancy in Jambi - Inesha Deariana; Suhair Quzwain; Anggelia Puspasari; Zakiyah Salim; Attiya Istarini (International Journal of Health and Social Behavior, 2026)
Ectopic pregnancy occurs when a fertilized ovum implants outside the uterine cavity and may cause life-threatening internal bleeding. Although the intrauterine device is an effective contraceptive method, pregnancies resulting from contraceptive failure have a greater likelihood of becoming ectopic. This study aimed to determine the relationship between intrauterine device use and the incidence of ectopic pregnancy at RSUD Raden Mattaher and RSI Arafah Jambi. An analytical observational design with a retrospective approach was applied. The samples were selected using total sampling from the medical records of first-trimester pregnant women treated between 2020 and 2024 who met the inclusion and exclusion criteria, resulting in 99 respondents. Statistical analysis showed a p-value of 0.013 (p < 0.05) and an odds ratio of 0.172. These findings indicate a statistically significant association between intrauterine device use and the incidence of ectopic pregnancy, with intrauterine device use associated with a lower risk of ectopic pregnancy in the study population. Therefore, intrauterine device use was significantly related to the incidence of ectopic pregnancy among patients at RSUD Raden Mattaher and RSI Arafah Jambi.